1963
DOI: 10.3382/ps.0420681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Response of Chicks to Virginiamycin and Other Antibiotics

Abstract: RESULTS AND DISCUSSIONExperiments 1 and 2 were run concurrently, using the same feed mixtures and chicks from the same commercial hatch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1972
1972
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…It may be postulated that the birds used in Experiment One developed an antibiotic-resistant microflora and thus negated the influence of the dietary antibiotics. On the other hand, antibiotics have been shown to exhibit their greatest effect on growth of chicks reared in an old environment (Coates et al, 1951;Hill et al, 1953;Combs and Bossard, 1963). Their data conflict with the results of Experiment One in which chicks were grown in contaminated quarters.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…It may be postulated that the birds used in Experiment One developed an antibiotic-resistant microflora and thus negated the influence of the dietary antibiotics. On the other hand, antibiotics have been shown to exhibit their greatest effect on growth of chicks reared in an old environment (Coates et al, 1951;Hill et al, 1953;Combs and Bossard, 1963). Their data conflict with the results of Experiment One in which chicks were grown in contaminated quarters.…”
Section: Resultscontrasting
confidence: 67%
“…The following reports constitute a number of excellent reviews: Cuthbertson, 1952;Braude et al, 1953;Jukes and Williams, 1953;Stokstad, 1954;Ewing, 1963; however, the comparative results obtained from the different laboratories vary considerably. Several investigators (Libby and Schaible, 1955;Sherman et al, 1959); Nelson et al, 1963;and Combs and Bossard, 1963) reported that continuous use of antibiotics resulted in a decrease in their effectiveness as growth promotants in chicks. In contrast, Bird (1968) observed no change in chick growth responses to antibiotics during the period of 1951-1968.…”
mentioning
confidence: 99%
“…The antimicrobial activity of virginiamycin was first reported by De Somer and Van Dijck (1955) and was subsequently shown several years later to have additional potential as a growth promoter in chickens when used at subtherapeutic levels (Eyssen et al, 1962;Eyssen and De Somer, 1963;Combs and Bossard, 1963). A number of more recent reports also provide evidence for the enhancement of growth rates and feed conversion ratios by dietary levels of virginiamycin ranging from 10 to 22 mg/kg of feed (March et al, 1978;Miles et al, 1984b;Buresh et al, 1986).…”
Section: Introductionmentioning
confidence: 91%
“…Virginiamycin is not active against the enterobacteriaceae and is not involved in resistance transfer among these microorganisms (Pantaleon and Chevrier, 1969). Eyssen and De Somer (1963) and Combs and Bossard (1963) reported that virginiamycin stimulated growth of chicks. March et al (1978) and Miles et al (1984) reported that virginiamycin stimulated growth and improved feed efficiency in broilers.…”
Section: Introductionmentioning
confidence: 97%